Building Husband and Wife Partnership Patterns Among Regional Parliament (DPRD) Members from the MubÄdalah Perspective - Supriyadi, Supriyadi; Zaelani, Abdul Qodir; Mahmudah, Siti; Jaâ€™far, Ahmad Khumedi (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This study aimed to analyze the husband and wife partnership pattern due to the wife's role as a member of the Regional Parliament (DPRD) from the mubÄdalah (reciprocity) perspective. The qualitative descriptive approach was adopted and data were collected through interviews and documentation of 6 female respondents of the DPRD members in Pesawaran Regency, Lampung Province. Respondents were selected using purposive sampling, while the parameters used to examine the husband and wife partnership pattern included division of domestic work, family financial support, and decision-making processes. The result showed an increase in the impact of the partnership pattern on household harmony, which was assessed using the interpersonal communication theory of Joseph A. Devito and Kyai Faqih's mubÄdalah theory. Furthermore, the division of domestic work among wives as DPRD members could be categorized into two groups. The first was the shared responsibility between husband and wife, while the second was the exclusive responsibility assigned to the wife without the involvement of the husband. In terms of financial support, some wives relied solely on their husbands, while others shared the responsibility. All respondents used the family deliberation approach for decision-making and they agreed on the importance of building a good partnership based on the mubÄdalah principles between husband and wife. MubÄdalah principle consisted of partnership, cooperation, reciprocity, and mutual understanding, which aimed to maintain household harmony.